Depressed older adults: an analysis of factors related to institutionalization and family support - Saintrain, Maria Vieira de Lima (2018)
Objective: To identify the prevalence of depression in older adults living in long-term care (LTC) facilities and its association with the reasons for institutionalization. Methods: Quantitative, cross-sectional study carried out in Fortaleza, Ceará, using a data collection instrument designed to perform clinical assessment of major depression, based on the Diagnostical and statistical manual of mental disorders (DSM-IV-TR) diagnostic criteria. It was also used to record secondary data obtained from the medical records of the older adult patients in order to complement information on the institutionalization context. Results: Of all older adults analyzed, 82 (34.6%) presented a diagnosis of major depression according to DSM-IV-TR criteria. As for the diagnosis of depression related to the LTC facility, there was a statistically significant difference between the two LTC facilities (p=0.042). With regard to the association between depression and institutionalization duration (p=0.001), it is important to highlight a higher percentage among older adults with up to three years of institutionalization (37.8% of the cases of depression), which suggests that a short period of separation from family and the process of adaptation to the new type of housing may constitute risk factors for the disease. Conclusion: The findings described above allude to the idea that institutionalization duration, lack of interpersonal relationships, loneliness and the fact that the older adults receive visits from family members in this period are risk factors for depression.